45,X/46,XY mixed gonadal dysgenesis: A case of successful sperm extraction - Flannigan, Ryan Kendrick; Chow, Victor; Ma, Sai; Yuzpe, Albert (Canadian Urological Association Journal, 2014)
Infertility is common among couples, about one third of cases are the result of solely male factors, and rarely abnormalities of genetic karyotypes are the root cause. Individuals with a 45X,/46,XY mosaiscism are rare in the literature and very few have fertile potential. We discuss a case of a 27-year-old male with known mixed gonadal dysgenesis, 50:50 split mosaiscism of 45,X/46,XY, presenting for evaluation of 1.5 year history of infertility. He demonstrated low volume non-obstructive azoospermia. Upon testicular biopsy, spermatozoa were extracted. These sperm were subjected to aneuploidy studies demonstrating 95.95% euploidy. The sperm were further assessed and placed in cryopreservation after being deemed sufficient for potential intracytoplasmic sperm injection. This is a unique case of viable sperm in a man with mixed gonadal dysgenesis, 45,X/46,XY mosaiscism.